2020
DOI: 10.1186/s40164-020-00173-3
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and inter-relationship of PD-L1 expression and tumour mutational burden across multiple types of advanced solid tumours in China

Abstract: Background: PD-L1 expression and tumour mutational burden (TMB) are both associated with the responses of multiple tumours to immune checkpoint inhibitor (ICI) therapy. However, their prevalence and correlations may differ in different types of advanced solid tumours. Methods: PD-L1 expression, TMB, and PD-1 + Tils (tumour-infiltrating lymphocytes) infiltration and their relationships were assessed in 6668 advanced solid tumour specimens across 25 tumour types. CD8 + T cell infiltration was analysed in 347 NSC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 57 publications
(52 reference statements)
2
21
0
Order By: Relevance
“…Detailed classification of tumor-infiltrating lymphocytes (TILs) and identification of cellular crosstalk in AML BM niche will provide important means of assistance based on existed mature chemotherapies [ 90 ]. By examining immune cell types can help to formulate personalized high-efficiency immunotherapy trials.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed classification of tumor-infiltrating lymphocytes (TILs) and identification of cellular crosstalk in AML BM niche will provide important means of assistance based on existed mature chemotherapies [ 90 ]. By examining immune cell types can help to formulate personalized high-efficiency immunotherapy trials.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that a high density of CD8+ cells was associated with a higher median OS time in 163 NSCLC patients who received durvalumab (P<0.01) (32). Some studies have also found that high infiltration of CD8+ T cells is correlated with a relatively good response in patients treated with ICIs (12,(19)(20)(21). A previous study found that the level of CD8+ T cells was significantly higher in patients achieving CR/PR than in those with SD/PD in melanoma (P < 0.0001) (32).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to TMB and PD-L1, multiple immune cell subsets have been assessed to determine their predictive value for immunotherapy outcomes in NSCLC (12,13,18). It was reported that the infiltration of CD8+ T cells was associated with ICI efficacy (12,(19)(20)(21). Tumor-associated macrophages (TAMs) are important immune cells in the tumor microenvironment (TME), as they mediate tumor progression by regulating TME (22).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, for these non-responders undergoing treatment, the PD-1-PD-L1 axis is not the sole speed-limiting step in the Cancer-Immunity Cycle [ 20 ]. A group of factors including other immune checkpoints [ 21 23 ], cancer neoantigens [ 24 26 ], gut microbiota [ 27 , 28 ], soluble MHC related molecules [ 29 ], and cytokines in the tumor microenvironment (TME) also affect anti-cancer immune response [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%